[ ( 3 + a ) × 3 + 3 × ( 3 + 3 : a ) ] : 3 - 3 × 3 + 3 : 3 = 2
( 9 + 3 a + 9 + 9 / a ) : 3 - 9 + 1 = 2
( 3 a + 9 / a + 18 ) : 3 = 2 - 1 + 9
( 3 a + 9 / a + 18 ) : 3 = 10
3 a + 9 / a + 18 = 10 x 3
3 a + 9 / a + 18 = 30
3 a² + 9 = a × ( 30 - 18 )
3 a² - 12 a + 9 = 0 l : 3
a² - 4 a + 3 = 0
Δ = 16 - 12 = 4
a₁ = ( 4 + √4) / 2 = 6 / 2 = 3
a₂ = ( 4 - 2 ) / 2 = 2 / 2 = 1
Verific
[ ( 3 + 1 ) × 3 + 3 × ( 3 + 3 : 1 ) ] : 3 - 3 × 3 + 3 : 3 =2 ( a = 1)
= ( 12 + 18 ) : 3 - 9 + 1 =
= 10 - 9 + 1 =
= 2
[ ( 3 + 3 ) × 3 + 3 × ( 3 + 3 : 3 ) ] : 3 - 3 × 3 + 3 : 3 = 2 ( a = 3)
= ( 18 + 12 ) : 3 - 9 + 1 =
= 10 - 9 + 1 =
= 2